COMUNIDADES LINGUÍSTICAS: UMA REFLEXÃO SOBRE A FRONTEIRA JAGUARÃO/RIO BRANCO - David Acosta, Vanessa; Giacomelli, Karina (Revista de Letras, 2024)
This work aims to reflect on languages that circulate in the border Jaguarão - Rio Grande do Sul-Brazil - Rio Branco / Cerro Largo-Uruguay, bringing to this study the linguistic situation of this border zone, showing that access to diverse varieties of language, situations and enunciative practices increase subjects’ discursive repertoire and their ability to interact and, consequently, their effective condition to practice citizenship, considering that borders are not only geographical and political, but also social and cultural and the contact of subjects is not only geographical, but also perceived in customs, culture and language. To carry out the study, bibliographic data were collected on the constitution of the concerned borders, as well as a study on how linguistic contact manifests itself in this space of enunciation. One may conclude that in addition to the pair of languages that mostly circulate on the border, there are other linguistic communities that also occupy this space, building the border’s identity. KEYWORDS: linguistic communities; linguistic contact; languages at the border.